Pendidikan Agama Islam untuk Anak Berkebutuhan Khusus di Sekolah Dasar Luar Biasa (SDLB) Negeri Cerme - Susilowati, Susilowati; Muizzuddin, Muizzuddin (Green Publisher Indonesia, 2024)
Children with special needs are often referred to as extraordinary children, special skills are needed in teaching children with special needs, where educators do not only convey advice to them, but educators must be more selective in observing the students behavior. The purpose of research isexplore how: (1) the education of children with special needs SDLBN Cerme. (2) the supporting factors of Islamic servants and the efforts made in Islamic religious education for special needs. The approach taken was using a qualitative approach, type a case. Data collection techniques performed using regular observations, interview and documentation. The research instrument was carried out by the researcher. Researcher use spiral data analysis, namelyresearchers must enterinto the analysis circle with data in the form of words (text), photos and left with a report as long as the researcher was still in spiral analysis, then the researcher interacted with several channels of analysis and took turns and kept turning. The research informants were: school principals, home parents, PAI teachers and student guardians, children with special needs and school operators. The results of the study show that (1) In carrying out the process of islamics religious education there are several religious activities such as flag ceremonies, congregational dhuha prayers, literacy, pondok Ramadhan and tilawatilqur’an. (2) Supportinng factors that influence Islamic religious education at SDLBN Cerme including: teachers, parents cooperation, motivation, interest in learning, the use of Indonesia orally or gestures, use of teaching aids, awarding of reward, as well as facilities and infrastructure. The inhibiting factors include: lack of concentration, problem in students, the lack of Islamic religious education teachers in these institutions.